THE INFLUENCE OF CHARACTER OF ROLE INTERACTION «THE MEDICAL WORKER – PATIENT» ON VALUE JUDGMENT OF QUALITY OF MEDICAL CARE TO THE PEOPLE LIVING WITH HIV - O. A. Chernyavskaya; E. A. Ioannidi (Медицинский вестник Юга России, 2015)
Purpose: to characterize role interaction ≪the medical worker – patient≫ in system of medical care to the people living with HIV to estimate their influence on value.Materials and methods: in 2012-2014 voluntary anonymous individual internal questioning of 187 HIV-positive people of the patient and 92 health workers from various treatment-and-prophylactic establishments of Volgograd and Volgograd region is carried out.Results: the characteristic of relationship of health workers and HIV is given – the infected patients arising in the course of performance of the professional roles by them their influence on value judgment of quality of medical care is established.Conclusion: monitoring of satisfaction of HIV – the infected patients of various treatment-and- prophylactic establishment by quality of medical care provided to them, development of the establishments which achieved the best indicators is required.